2021
DOI: 10.1002/cctc.202101510
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Catalytic Activity from 13CCH Alkylidene Chemical Shift in Cationic Tungsten Oxo Alkylidene N‐Heterocyclic Carbene Complexes

Abstract: A series of cationic tungsten oxo alkylidene N-heterocyclic carbene (NHC) complexes was synthesized and structurally characterized by single crystal X-ray diffraction. The 13 C NMR chemical shifts of the alkylidene C atoms of these complexes were correlated with the diamagnetic, paramagnetic and spinorbit chemical shifts calculated by DFT. A good correlation (R 2 = 0.90) between the DFT isotropic chemical shifts and the experimental chemical shift as well as a strong correlation between the DFT isotropic chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The same trend for the low dose required to gel holds for complexes bearing an oxo ligand ( W-2 , W-5 ). In fact, previous studies showed that tungsten oxo alkylidene NHC complexes possess a remarkably high activity in olefin metathesis. , On the other hand, high doses were required for complexes without electron-withdrawing fluorinated moieties or oxo ligands ( W-6 – W-10 ). Compared to most aryl imido complexes, a tungsten t Bu-imido precatalyst ( W-10 ) required long irradiation until solidification of the mixture commenced, which is in line with previous observations on the poor productivity of tungsten t Bu-imido alkylidene NHC complexes .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The same trend for the low dose required to gel holds for complexes bearing an oxo ligand ( W-2 , W-5 ). In fact, previous studies showed that tungsten oxo alkylidene NHC complexes possess a remarkably high activity in olefin metathesis. , On the other hand, high doses were required for complexes without electron-withdrawing fluorinated moieties or oxo ligands ( W-6 – W-10 ). Compared to most aryl imido complexes, a tungsten t Bu-imido precatalyst ( W-10 ) required long irradiation until solidification of the mixture commenced, which is in line with previous observations on the poor productivity of tungsten t Bu-imido alkylidene NHC complexes .…”
Section: Results and Discussionmentioning
confidence: 99%
“…All bond lengths and angles are similar to those observed for five-coordinate cationic W oxo alkylidene NHC complexes. 17 …”
Section: Resultsmentioning
confidence: 99%
“…All bond lengths and angles are similar to those observed for ve-coordinate cationic W oxo alkylidene NHC complexes. 17 On a nal note regarding the synthesis of cationic Mo oxo alkylidene complexes, the synthesis of further species bearing uorinated alkoxides starting from aryloxide complexes Mo-6 and Mo-7 have been attempted using HOC(CF 3 ) 3 . Unfortunately, the reactions proved unsuccessful, and no conversion was observed.…”
Section: Synthesis Of Molecular Catalystsmentioning
confidence: 99%
“…We already reported on the synthesis of [W-(O)Cl 2 (CHCMe 2 Ph)(PPhMe 2 )(IMes)] [12] ( (B(Ar F' ) 4 À = tetrakis(pentafluorophenyl)borate, Scheme 3), accessible via crystallization from CH 2 Cl 2 /diethyl ether. [15] Diethyl ether-coordinated 17 . Et 2 O crystallizes in the triclinic space group P � 1with a = 1111.85 pm, b = 1553.17 pm, c = 1893.34 pm, α = 92.94, β = 99.14 °, γ = 109.88 °, Z = 2 (Figure 7).…”
Section: Tungsten Oxo Alkylidene Nhc Complexes 14-17 Et 2 Omentioning
confidence: 99%
“…[12] Immobilization of cationic tungsten oxo alkylidene NHC complexes [12] on silica thermally treated at 700 °C (silica 700 ) offered access to supported cationic tungsten oxo/imido alkylidene NHC catalysts [13] with which turnover numbers (TONs) of > 1,200,000 were achieved in the homometathesis of propene. [14] Based on these findings, we developed new synthetic strategies for tungsten oxo alkylidene NHC complexes, [15] including the addition of water to tungsten alkylidyne NHC progenitors, [16] a route that has successfully been extended to the synthesis of tungsten sulfido alkylidene NHC complexes. [16] In the transition state, cationic molybdenum imido complexes adopt a trigonal bipyramidal (TBP) transition state with the molybdacyclobutane trans to the NHC, [17] while cationic tungsten oxo catalysts can adopt both, a TBP or a square pyramidal (SP) transition state, again with the tungstacyclobutane trans to the NHC.…”
Section: Introductionmentioning
confidence: 99%